2020
DOI: 10.1016/j.fawpar.2020.e00087
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcosis in humans and animals in Southern Africa Development Community countries: A systematic review

Abstract: The taeniid Echinococcus is the causative agent of the zoonotic disease echinococcosis/hydatidosis and is associated with economic losses in livestock production. This review summarizes available scientific literature on circulating species of Echinococcus in humans, wild and domestic animals in countries of Southern Africa Development Community, and identifies knowledge gaps and recommend research priorities. Data were systematically accessed from Google Scholar, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…In the present study, the prevalence of CE in East Azerbaijan of Iran was relatively the same reports from neighboring countries in the Middle East such as Iraq: 7.3% (Abdulhameed et al 2018) Syria: 2.8% (Seimenis 2003) Saudi Arabia: 2.33% (Adbel-Baki et al 2018) but differs from those reported in other studies in Turkey: 30.6, Spain: 0.1 %, France: 0.004%, Italy: 21%, Romania: 11-13%, Greece:29%, Kenya: 10.8% and Southern Africa (Miambo et al 2020;Tamarozzi et al 2020).…”
Section: Discussion and Conclusion And Recommendationsmentioning
confidence: 76%
“…In the present study, the prevalence of CE in East Azerbaijan of Iran was relatively the same reports from neighboring countries in the Middle East such as Iraq: 7.3% (Abdulhameed et al 2018) Syria: 2.8% (Seimenis 2003) Saudi Arabia: 2.33% (Adbel-Baki et al 2018) but differs from those reported in other studies in Turkey: 30.6, Spain: 0.1 %, France: 0.004%, Italy: 21%, Romania: 11-13%, Greece:29%, Kenya: 10.8% and Southern Africa (Miambo et al 2020;Tamarozzi et al 2020).…”
Section: Discussion and Conclusion And Recommendationsmentioning
confidence: 76%
“…were found in wild mammals in Namibia, the highest known diversity in wildlife on the African continent followed by Kenya ( Kagendo et al, 2014 ; Romig et al, 2011 ) and representing all Echinococcus spp. known to occur in Africa ( Deplazes et al, 2017 ; Miambo et al, 2020 ; Mogoye et al, 2013 ). This high diversity in Namibia is unlikely to be extraordinary but might reflect the scarcity of records in other countries, at least for southern Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Also, more attention is needed in analysing and managing the risk of potential diseases including CE. Very little is known about the CE situation in humans in Namibia, and most other countries of southern Africa ( Miambo et al, 2020 ), thus further investigations are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…"G nomenclature" could not be applied the lion strain due to lack of biological sample. [5][6][7][8][9][10] Today, some evidence exists which supports that G2 is a sub-group of G1 (using cox1 sequences) or G3 (using nad1 sequences), [7,9] and G1-G3 genotype is considered as a single species as E. granulosus sensu stricto. In addition, the G9 genotype is now accepted as a microvariant of G7.…”
Section: Introductionmentioning
confidence: 99%